Prevalence of antibodies against Toxoplasma gondii among Brazilian white-eared opossums (Didelphis albiventris) - Fornazari, Felipe [UNESP]; Teixeira, Carlos Roberto [UNESP]; da Silva, Rodrigo Costa [UNESP]; Leiva, Maristela [UNESP]; de Almeida, Silvio Cesar [UNESP]; Langoni, Hélio [UNESP] (Elsevier B.V., 2011)
Considering that Toxoplasma gondii is a parasite of global importance which affects several animal species including humans, the current study aimed to investigate the prevalence of antibodies against T. gondii among 72 white-eared opossums (Didelphis albiventris) from Botucatu Municipality (22 degrees 53'S 48 degrees 26'W), São Paulo State, Brazil. The investigation was carried out from January 2008 to December 2009, when the animals had their blood samples collected and subjected to the modified agglutination test (MAT); 12 specimens had brain samples bioassayed in mice. Seroprevalence was 5.5% (n = 4) and bioassays were negative. Older animals had higher prevalence of antibodies against T. gondii. Opossums in closer contact with the urban environment are likely more exposed to T. gondii than animals from the sylvatic environment. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: White-eared opossum; Didelphis albiventris; Toxoplasma gondii; Wild animals; MAT